Legacy of Deaths in Muhamed Enveri Kadic’s Chronicle (1800-1815) - Omanović-Veladžić, Alma (Prilozi za orijentalnu filologiju, 2017)
Among numerous manuscripts that Kadic copied in his Chronicle, we find a large amount of information on the deceased residents, mostly from Sarajevo mahala’s or villages that belonged to Sarajevo kadiluk. There is a section in the Kadic’s Chronicle marked with “Vefeyāt”. Within this section we find notes that contain lists of the legacy of the dead, which Kadic took over from Sarajevo court registers for the period between 1800. and 1815. These lists of assets provide a rich and valuable material for historians, ethnographers and other researchers for the study of the economic condition of our nation at that time. The paper presents forty-four notes that treat the legacy of deaths for the same period. Thirty-seven notes refers to adult male Muslims, three to non-Muslims and four to court sessions hearings deceased female for that were wealthy.